COMPANIES FIND THEM COSTLY WHY QUIT EMPLOYING SMOKERS? (Tufts Archival Research Center, 2007)
Newspaper column reporting a business trend of not employing smokers. Presents examples of companies that have stopped employing smokers or have encouraged smokers to quit. Discusses monetary incentives given to some smokers to quit. Mentions costs of smoking to employers.